Gestión de crisis corporativa en el sector aerocomercial: caso Viaje Lindo Airlines - Mestanza Rivera, Luis Miguel (2019)
The concern to manage the intangible values of companies responds to the need to differentiate more and more and face the complexity of the environment (interactions). In that sense, and following the objectives of the company Viaje Lindo Airlines, the Dircom approach turns out to be an efficient alternative to manage the current communication crisis. For this, a short and medium term crisis management plan will be generated, focused on the different stakeholders of the organization, and then develop positioning strategies that reaffirm the company's attributes. It´s worth mentioning that digital tools will be integrated to address this corporate crisis.